2018
DOI: 10.21315/mjms2018.25.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-microbial Activity of Aqueous Quercus infectoria Gall Extract against Pathogenic Leptospira

Abstract: BackgroundQuercus infectoria gall extract is known to have broad spectrum anti-microbial activity in vitro. This study was conducted to determine the anti-microbial activity of Q. infectoria gall extract against pathogenic Leptospira and to evaluate the morphological changes of extract-treated cells using a scanning electron microscope (SEM).MethodsA two-fold serial microdilution broth assay was used to determine the minimum inhibitory concentration (MIC) of aqueous Q. infectoria gall extract against the L. in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The antimicrobial activity was evidenced against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhimurium , and Candida albicans , and the results showed disinfection of eggshell microbial contamination, by immersion in 1% QIE solution, sharply reduced total colony count, yeasts, and molds, and Enterobacteriaceae, E. coli , and S. aureus were completely inhibited after 60 min of immersion in QIE [ 102 ]. Another investigation demonstrated that the extract of the Quercus infectoria gall possesses antimicrobial activity against Leptospira interrogans serovar Javanica and Leptospira interrogans serovar Icterohaemorrhagiae with MIC values of 0.125 mg/mL [ 103 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…The antimicrobial activity was evidenced against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhimurium , and Candida albicans , and the results showed disinfection of eggshell microbial contamination, by immersion in 1% QIE solution, sharply reduced total colony count, yeasts, and molds, and Enterobacteriaceae, E. coli , and S. aureus were completely inhibited after 60 min of immersion in QIE [ 102 ]. Another investigation demonstrated that the extract of the Quercus infectoria gall possesses antimicrobial activity against Leptospira interrogans serovar Javanica and Leptospira interrogans serovar Icterohaemorrhagiae with MIC values of 0.125 mg/mL [ 103 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Alternative therapies for the treatment of leptospirosis, such as the use of validated medicinal plants, are still limited. However, in the last decade, some scientific studies have aimed to study the mechanisms of action of plants and their bioactive compounds in the treatment of leptospira pathogens, both to elucidate the mechanisms of action (Chandan et al, 2012;Divya et al, 2013;Seesom et al, 2013;Mustafa et al, 2018).…”
Section: Medicinal Plants Used In Leptospirosis Studiesmentioning
confidence: 99%
“…Although the extract compositions present variations, all these plants in their respective studies showed positive results in treatment of pathogenic serovars of Leptospira spp. (Saravan et al, 2012;Chandan et al, 2012;Seesom et al, 2013;Nelson et al, 2013;Divya et al, 2013;Chander et al, 2015;Mustafa et al, 2018).…”
Section: Medicinal Plants Used In Leptospirosis Studiesmentioning
confidence: 99%
“…Quercus infectoria (Olivier) (Fagaceae) is one of the medicinal plants traditionally used in folk medicines for post-partum medication and various ailments (Umachigi et al, 2008;Vuthikunchai & Suwalak, 2008;Aroonrerk & Kamkaen, 2009;Jamal et al, 2011). The galls of the plant have a broad spectrum of antimicrobial properties (Hussein et al, 2000;Sawangjaroen et al, 2004;Sawangjaroen & Sawangjaroen, 2005;Ozbilgin et al, 2013;Baharuddin et al, 2014;Kheirandish et al, 2016;Mustafa et al, 2018;Nik Mat Zin et al, 2019). Our recent finding reported that the gall acetone crude extract possesses a promising antimalarial activity in vitro (IC 50 = 5.85 ± 1.90 μg/mL) against the chloroquine-sensitive strain (3D7) of P. falciparum (Nik Mat Zin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%